Desain Pendidikan Akhlak di Sekolah Menengah Pertama 2 Jember - Royani, Ahmad (Tadbir : Jurnal Studi Manajemen Pendidikan, 2018)
The emergence of the counter-productive in the world of education has led to the emergence of symptoms among the youths, even the adults, which show that they ignore the moral values and manners needed in a civilized society. Concerns about moral decadence, it is like a double-edged knife. If you are looking for the root of the problem on others, it is essentially be the root of the problem of yourself; so, blaming others means also blaming themselves. Thus, it is necessary to find the solution and the moral education in an appropriate action. This research on " Model of Moral Education in SMP 2 Jember" is done based on these concerns. The results of this study address that the design of applicative-integrative moral education in SMPN 2 Jember is applied into four models; first, it is integrated with the teaching and learning activities; second, it is included in the school culture that covering the school routine activities which are already programmed, and also the spontaneous activity, the exemplary of the educators and education personnel, and the physical and non-physical conditioning; third, the extra-curricular activities as the additional activity in SMPN 2 Jember; and fourth, comunity-based activities that involve the parents and societies in the implementation of applicative-integrative moral education. Key word: Education, Akhlak , Scholl